Reviews and notices - Sandra Freeman; Michael Jamieson; Christopher Murray; Ulf Danatus; Göran Kjellmer; Anne Moskow; Ronald Paul; Frank-Michael Kirsch; Bo Andersson; Gustav Korlén; Elisabeth Tegelberg; Börje Schylter; et al. (Moderna Språk)
Includes the following reviews: pp. 96-97. Sandra Freeman. Griffiths, T.R. & Llewellyn, M. (eds.), British and Irish Women Dramatists Since 1958.